Two new Themistoclesia (Ericaceae: Vaccinieae) from Peru - Luteyn, James L.; Ortiz, Edgardo M.; Pedraza-Peñalosa, Paola (Phytotaxa, 2024)
Themistoclesia david-smithii and T. gigantiflora (Ericaceae: Vaccinieae), from the Yanachaga-Chemillén National Park located in central Peru, are described and illustrated.